2002
DOI: 10.1177/1357633x0200800301
|View full text |Cite
|
Sign up to set email alerts
|

Realtime Transfer of Live Video Images in Parallel with Three-Dimensional Modelling of the Surgical Field in Computer-Assisted Telesurgery

Abstract: We have carried out three-dimensional, computer-assisted, functional endoscopic sinus telesurgery. Surgeons at different locations up to 300 km apart could not only see and transfer video images but also transfer three-dimensional computer models and manipulate them in realtime during surgery. Two different approaches were used. In the first telesurgery procedure we used M-JPEG compression and transmitted the data using fibre optic connections (ATM OC-3) at a bandwidth of 155 Mbit/s. In the second telesurgery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…Of course, we know that using this novel approach in the 21 st century medicine would enable all systems of simulated reality to share the ability and offer the user/tele-user [10,11] (Figure 7) to move and act within the apparent worlds instead of the real world, as described in our previous publications6 and demonstrated in the OR during operative procedure on a patient with maxillary sinus cyst protruding to the oral cavity through the oroantral fistula. In line with our previous experimental studies published in the past two decades [1,10,12] and experiences reported by other authors [13][14][15], our primary objective was to establish whether this new approach in visualization of human anatomy would avoid the risks associated with real endoscopy and minimize procedural difficulties when used prior to performing an actual endoscopic examination [16]. Therefore, bearing in mind the definition of VR ("impression of being present in a virtual environment, such as virtual/tele-VE of the patient's head that does not exist in reality is called VR", we tested the possibility to derive spatial cross-sections at selected anatomic cutting planes in rhino-surgery, which would provide an additional insight into the internal regions observed [6].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Of course, we know that using this novel approach in the 21 st century medicine would enable all systems of simulated reality to share the ability and offer the user/tele-user [10,11] (Figure 7) to move and act within the apparent worlds instead of the real world, as described in our previous publications6 and demonstrated in the OR during operative procedure on a patient with maxillary sinus cyst protruding to the oral cavity through the oroantral fistula. In line with our previous experimental studies published in the past two decades [1,10,12] and experiences reported by other authors [13][14][15], our primary objective was to establish whether this new approach in visualization of human anatomy would avoid the risks associated with real endoscopy and minimize procedural difficulties when used prior to performing an actual endoscopic examination [16]. Therefore, bearing in mind the definition of VR ("impression of being present in a virtual environment, such as virtual/tele-VE of the patient's head that does not exist in reality is called VR", we tested the possibility to derive spatial cross-sections at selected anatomic cutting planes in rhino-surgery, which would provide an additional insight into the internal regions observed [6].…”
Section: Discussionsupporting
confidence: 92%
“…The best way to predict the future is to create it ourselves. Today, our understanding of the anatomy in humans could be deceived, where we can replace the true reality with the simulated reality [1][2][3] that enables precise, safer and faster diagnosis [4], as well as surgery, creating an impression of another 'external' world around the man [5,6]. Through the concept of simulated reality, almost the same environment can be achieved as in true reality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ownership of powerful technologies such as antibiotics and anaesthetic by doctors are an early example of their diversification, which contributed to their strength and autonomy as a profession (Willis 1983). Computer technology has facilitated the expansion of the roles of surgeons, through, for instance, the use of video laparoscopy (Klapan et al 2002, Zetka 2003). Podiatrists have developed the concept of podiatric biomechanics (Borthwick 1999).…”
Section: Intra‐disciplinary Changementioning
confidence: 99%
“…Mentees may benefit from guidance from faculty of a similar background at a different institution, or even outside of OHNS, when considering social identity in relation to professional development. Although mentoring at a distance has existed for many years, including telementoring to improve surgical skills, [26][27][28] virtual mentorship has greatly accelerated during the COVID-19 pandemic, and a variety of virtual otolaryngology experiences have emerged. [29][30][31] Efforts are needed to ensure that these opportunities are delivered equitably.…”
Section: Near-peer and Reverse Mentorshipmentioning
confidence: 99%